Male figure with folded hands on the Torana - Temples of India Project Team (Jio Institute, 2024)
The male figure on the other pillar of the torana (ornamental gateway) is depicted in the same posture with folded hands. He is also adorned with heavy jewellery and bears the distinctive mark of Jaina deities on his chest. He is accompanied by an attendant.